2020
DOI: 10.1101/2020.05.04.076596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mycobacterium marinumphthiocerol dimycocerosates enhance macrophage phagosomal permeabilization and membrane damage

Abstract: 17 18 Phthiocerol dimycocerosates (PDIMs) are a class of mycobacterial lipids that 19 promote virulence in Mycobacterium tuberculosis and Mycobacterium marinum. It 20 has recently been shown that PDIMs work in concert with the M. tuberculosis Type 21 VII secretion system ESX-1 to permeabilize the phagosomal membranes of infected 22 macrophages. As the zebrafish-M. marinum model of infection has revealed the 23 critical role of PDIM at the host-pathogen interface, we set to determine if PDIMs 24 contributed to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…PDIM has been suggested to interact with the protein substrates of the type VII secretion system ESX-1, including EsxA ( Barczak et al, 2017 ). PDIM and EsxA are both required for cytosolic escape from phagolysosomes ( Osman et al, 2020 ; Quigley et al, 2017 ; van der Wel et al, 2007 ), where PDIM is suggested to enhance the pore-forming activity of EsxA through its ability to infiltrate macrophage membranes ( Augenstreich et al, 2017 ). Thus, we hypothesized that PDIM’s localization may be dependent on EsxA’s pore forming ability.…”
Section: Resultsmentioning
confidence: 99%
“…PDIM has been suggested to interact with the protein substrates of the type VII secretion system ESX-1, including EsxA ( Barczak et al, 2017 ). PDIM and EsxA are both required for cytosolic escape from phagolysosomes ( Osman et al, 2020 ; Quigley et al, 2017 ; van der Wel et al, 2007 ), where PDIM is suggested to enhance the pore-forming activity of EsxA through its ability to infiltrate macrophage membranes ( Augenstreich et al, 2017 ). Thus, we hypothesized that PDIM’s localization may be dependent on EsxA’s pore forming ability.…”
Section: Resultsmentioning
confidence: 99%
“…The combined action of PDIM and ESX-1 in phagosomal membrane disruption was confirmed in Mma [83]. Indeed, a mutant defective in MmpL7, the transporter of PDIM, demonstrated decreased phagosomal permeabilization similarly to the ESX-1 deletion mutant [83] (Fig. 3a).…”
Section: Kansassii Esx-1 /mentioning
confidence: 70%
“…For instance, EsxA membrane permeabilization is potentiated by the phthiocerol dimicerosate (PDIM), which are cell-surface associated lipids capable of disrupting the biochemical properties of host membranes [81,82]. The combined action of PDIM and ESX-1 in phagosomal membrane disruption was confirmed in Mma [83]. Indeed, a mutant defective in MmpL7, the transporter of PDIM, demonstrated decreased phagosomal permeabilization similarly to the ESX-1 deletion mutant [83] (Fig.…”
Section: Kansassii Esx-1 /mentioning
confidence: 92%
“…Immunization of mice with dewaxed whole‐cell M. ulcerans antigens, but not formalin‐fixed bacilli, caused an increase in M. ulcerans ‐specific IgG titers, suggesting that these lipidic structures concealed antigens from the host immune system 36 . Accordingly, phthiocerol dimycocerosates (PDIMs) from M. tuberculosis and M marinum were shown to mask underlying pathogen‐associated molecular patterns (PAMPs), allowing evasion from Toll‐like receptor (TLR) signaling pathways and contributing to phagosome evasion in conjoint with ESAT‐6 secretion systems (ESX) ‐1 37‐41 . Other experimental studies with M. tuberculosis show that PDIM molecules can be transferred to the membranes of macrophages and promote biophysical changes that influence cellular processes such as phagocytosis 42 .…”
Section: Lessons and Questions On The Origin Of The Speciesmentioning
confidence: 99%